Island food systems in transition: Strengthening Indigenous food systems in Solomon Islands - Eriksson, Hampus; Tikai, Pitakia; M, Pelomo; Gomese, Chelcia; Ride, Anouk; Hunnam, Kimberly; Bonis-Profumo, Gianna; Siota, Faye Aborina; Notere Boso, Delvene; Wate, Jillian Tutuo (WorldFish, 2023)
This brief defines a vision for an island food system centered on rural food system actors and Indigenous foods. It provides the foundation for a new partnership program between the Kastom Gaden Association and WorldFish in Solomon Islands. This partnership will work towards implementing the island food systems vision.